Geometric Modeling and Imaging--New Trends (GMAI'06)
DOI: 10.1109/gmai.2006.29
|View full text |Cite
|
Sign up to set email alerts
|

Image Retrieval of Songket Motifs Using Simple Shape Descriptors

Abstract: Songket is a traditional handwoven cloth of the Malays and its beauty lies on the design of the songket motifs intricately woven on the cloth. Even though color is a feature of the motif, shape is more important in determining the type of the motifs. This paper describes and tests the efficiency of retrieving songket motifs images using different combination of five geometric shape descriptors. Even though there are many existing approaches of shape-based image retrievals, the goal of this paper is to take adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…C. Shahabi and M. Safar, compare performance of boundary based methods for shape representation and retrieval: Fourier descriptors method FD (based on objects' shape radii), grid-based method GB (based on chain codes) in paper [10]. Combination of different percentages of five geometric shape descriptors are experimented by N. Jamil, et al in paper [11] . This paper experiments on the combinations of the Eccentricity, Rectangularity, Compactness, Convexity, Solidity.…”
Section: Related Workmentioning
confidence: 99%
“…C. Shahabi and M. Safar, compare performance of boundary based methods for shape representation and retrieval: Fourier descriptors method FD (based on objects' shape radii), grid-based method GB (based on chain codes) in paper [10]. Combination of different percentages of five geometric shape descriptors are experimented by N. Jamil, et al in paper [11] . This paper experiments on the combinations of the Eccentricity, Rectangularity, Compactness, Convexity, Solidity.…”
Section: Related Workmentioning
confidence: 99%
“…Out of many geometric features that have been proposed by various authors~Jain, 1989; Sonka et al, 1999;Jamil et al, 2006;Russ, 2007;Sarfraz & Ridha, 2007!, it has been observed through our studies~Pattan et al, 2009, 2010a, 2010b! that the two geometric shape features, namely, diam-eter_ratio and area_ratio, provide better classification results.…”
Section: Feature Extractionmentioning
confidence: 99%
“…Content-based image retrieval [6] field has been rather popular among researchers through a rapid study along with other popular research areas such as Database Management, Natural Language Processing, Signal Processing, Computer Vision, Network Systems and Human-Computer Interaction [7]. Since studies on the field of image retrieval have proliferated, the main issue is how to expect the user's preferences [8] to the result of the image obtained through the image retrieval system [9], [10], [11]. Various models of image feature extraction were introduced through the implementation of the development on a variety of retrieval systems.…”
Section: Introductionmentioning
confidence: 99%
“…The features mentioned are part of the basic content-based image retrieval technique. All these techniques can assist the process of near-duplicate image entirely, as evidenced by various studies that have been carried out [10], [12], [13], [14]. However, the techniques involved in www.ijacsa.thesai.org CBIR face obstacles in processing image datasets in highdimensional clusters [15], [16], [17].…”
Section: Introductionmentioning
confidence: 99%